2011
DOI: 10.1111/j.1600-0897.2010.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Cytokine Production in Peripheral Blood Lymphocytes: A Comparison of Values in Infertile and Fertile Women

Abstract: Cytokines produced by Th lymphocytes are important in orchestrating the immune response during conception, and Th-cell dysregulation could be a reason for infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Interestingly, IL-6 levels were posited to play a role in unexplained infertility; women with infertility showed significantly higher IL-6 levels when compared with the fertile group (66). With regard to TNF, infertile women had a greater intracellular (IC) production of TNF- α, and higher ratios of TNF- α/IL-2, TNF- α/IL-4, TNF- α/ IFN-γ when compared to the fertile group (67). Idiopathic infertile and immune-infertile groups showed greater TNF- α concentrations from cervical mucus (but not from sera) compared to fertile groups, with immune-infertile groups having greater TNF- α concentrations compared to the idiopathic groups (68).…”
Section: How Might Sleep Affect Fertility?mentioning
confidence: 99%
“…Interestingly, IL-6 levels were posited to play a role in unexplained infertility; women with infertility showed significantly higher IL-6 levels when compared with the fertile group (66). With regard to TNF, infertile women had a greater intracellular (IC) production of TNF- α, and higher ratios of TNF- α/IL-2, TNF- α/IL-4, TNF- α/ IFN-γ when compared to the fertile group (67). Idiopathic infertile and immune-infertile groups showed greater TNF- α concentrations from cervical mucus (but not from sera) compared to fertile groups, with immune-infertile groups having greater TNF- α concentrations compared to the idiopathic groups (68).…”
Section: How Might Sleep Affect Fertility?mentioning
confidence: 99%
“…Some studies speculate that insufficient sleep may affect women's fertility through impaired immunity ( 47 ). During sleep deprivation, increased cytokine and immune inflammatory reaction marked by TNF and IL-6 were observed ( 53 – 55 ), high levels of IL-6 and TNF were considered to be related to female infertility ( 56 , 57 ). In a previous study of males, it was found that a short sleep duration was associated with a reduction in semen quality ( 58 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ως προς την ενδοκυττάρια παραγωγή κυτταροκινών, σε πρόσφατη in vitro μελέτη με λεμφοκύτταρα υπογόνιμων γυναικών, διαπιστώθηκε στατιστικά σημαντική αύξηση της ενδοκυττάριας παραγωγής TNF-, IL-2, IFNαλλά και IL-4, καθώς και υψηλότεροι λόγοι TNF-α/IL-2, TNF-α/IL-4 και TNFα/IFN-γ συγκριτικά με την ομάδα γόνιμων γυναικών 160 .…”
Section: συζητησηunclassified